The magical snowflake - Ford, Bernette G. (Boxer Books, 2023)
"It's the middle of winter, it's very cold, and Ori and her friends want to play outside. But there's no snow! Ori makes a wish, and soon a special snowflake brings delight to an entire town." -- Provided by publisher.